Pengaruh Moral Pajak, Sanksi Perpajakan, Dan Biaya Kepatuhan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Pelaku Ekonomi Kreatif Sub-Sektor Fashion Malang Raya - Nurul Qomariah; Jeni Susyanti; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to determine the effect of tax morale, tax sanctions and tax compliance costs on individual taxpayer compliance with creative economy actors in the fashion sub-sector of Malang raya city. Determination of the sample in this study using purposive sampling technique, so that the number of samples can be determined as many as 70 respondents who fit the criteria. The analytical tool used in this research is multiple linear regression analysis. The results showed that tax morale, tax sanctions and tax compliance costs simultaneously had a significant effect on individual taxpayer compliance with creative economy actors in the fashion sub-sector of Malang raya city. The variables of tax morale, tax sanctions and tax compliance costs have a significant and positive effect on individual taxpayer compliance with creative economy actors in the fashion sub-sector of Malang Raya City. Keywords: Creative Economy Actors in Malang raya city Fashion Sub-Sector, Tax Morale, Tax Sanctions and Tax Compliance costs, Taxpayer Compliance.